Cationic Polymer-Coated Magnetic Nanoparticles with Antibacterial Properties: Synthesis and In Vitro Characterization - Anastasiia B. Shatan; Vitalii Patsula; Aneta Dydowiczová; Kristýna Gunár; Nadiia Velychkivska; Jiřina Hromádková; Eduard Petrovský; Daniel Horák (MDPI AG, 2021)
Uniformly sized magnetite nanoparticles (Dn = 16 nm) were prepared by a thermal decomposition of Fe(III) oleate in octadec-1-ene and stabilized by oleic acid. The particles were coated with Sipomer PAM-200 containing both phosphate and methacrylic groups available for the attachment to the iron oxide and at the same time enabling (co)polymerization of 2-(dimethylamino)ethyl methacrylate and/or 2-tert-butylaminoethyl methacrylate at two molar ratios. The poly[2-(dimethylamino)ethyl methacrylate] (PDMAEMA) and poly[2-(dimethylamino)ethyl methacrylate-co-2-tert-butylaminoethyl methacrylate] [P(DMAEMA-TBAEMA)] polymers and the particles were characterized by 1H NMR spectroscopy, size-exclusion chromatography, transmission electron microscopy, dynamic light scattering, thermogravimetric analysis, magnetometry, and ATR FTIR and atomic absorption spectroscopy. The antimicrobial effect of cationic polymer-coated magnetite nanoparticles tested on both Escherichia coli and Staphylococcus aureus bacteria was found to be time- and dose-responsive. The P(DMAEMA-TBAEMA)-coated magnetite particles possessed superior biocidal properties compared to those of P(DMAEMA)-coated one.